일차 쇼그렌증후군 환자에서 안구표면염색점수와 침샘 신티그래피 - 박선경(Sun Kyoung Park), 강규동(Kui Dong Kang), 김현승(Hyun Seung Kim), 황형빈(Hyung Bin Hwang) (Daihan angwa haghoi jabji, 2020)
목적: 눈마름 임상증상을 보이는 일차 쇼그렌증후군(Sjögren’s Syndrome) 환자에서 안구표면염색점수와 정량화한 침샘 신티그래피지표 간의 상관관계 및 진단적 가치에 대해 분석하고자 한다. 대상과 방법: 2017년 7월부터 2019년 4월까지 류마티스내과에서 의뢰된 눈마름 임상증상을 보이는 쇼그렌 및 비쇼그렌증후군의 성인 51명의 의무기록을 후향적으로 검토하였으며, 일차 쇼그렌증후군과 비쇼그렌증후군 간에 안구표면염색점수와 침샘 신티그래피 각 지표의 차이가 있는지에 대한 비교에는 각각 Mann Whitney U-test 및 student t-test를 사용하였고, 안구표면염색점수와 침샘 신티그래피 지표 간의 상관분석은 Spearman correlation을 사용하였다. 결과: 안구표면염색점수(p=0.021), 귀밑샘의 excretion fraction (p=0.022), 턱밑샘의 excretion fraction (p=0.045)은 일차 쇼그렌증후군과 비쇼그렌증후군 두 군 간에 통계적으로 유의한 차이가 있었으며, 턱밑샘의 uptake ratio (rho=-0.369, p=0.008), 턱밑샘의 excretion fraction (rho=-0.359, p=0.010)은 안구표면염색점수와 통계적으로 유의한 음의 상관관계를 보였다. 결론: 안구표면염색점수는 일차 쇼그렌증후군에서 건성안의 정도를 평가하는 데에 있어서 표준진단법이며, 일차 쇼그렌증후군 환자가 초기에 눈마름 증상을 호소하지 않아도 침샘 신티그래피상에서 기능저하가 관찰될 때 반드시 안구표면병변의 유무를 확인해야 할 것이다. Purpose: To analyze the correlation between the ocular surface staining score and indices of salivary gland scintigraphy in patients with primary Sjögren's syndrome and dry eye symptoms, and to evaluate the diagnostic value of these indices. Methods: The patients were 51 adults with primary Sjögren's syndrome or non-Sjögren's syndrome plus dry eye symptoms, who were referred to our ophthalmology clinic for evaluation of the degree of dry eye at the Department of Rheumatology, from July 2017 to April 2019. The Mann-Whitney U test and student’s t-test were used for analyzing the ocular surface staining score and quantitative indices of salivary gland scintigraphy, respectively, in the primary Sjögren's syndrome and non-Sjögren's syndrome patients. Spearman correlation was used to analyze the correlations of ocular surface staining score with salivary scintigraphy indices. Results: The ocular surface staining score (p = 0.021), parotid gland excretion fraction (p = 0.022), and submandibular gland excretion fraction (p = 0.045) were significantly different between the primary Sjögren's syndrome and non-Sjögren's syndrome patients. The submandibular gland uptake ratio (r = -0.369, p = 0.008) and submandibular excretion fraction (r = -0.359, p = 0.010) were significantly negatively correlated with ocular surface staining scores. Conclusions: The ocular surface staining score was identified as the gold standard for evaluating the degree of dry eye in primary Sjögren's syndrome patients. If salivary gland dysfunction is identified by salivary gland scintigraphy, ocular surface staining should be performed to confirm the presence of ocular surface lesions, regardless of the presence of dry eye symptoms. KCI Citation Count: 0